2021
DOI: 10.1002/slct.202004237
|View full text |Cite
|
Sign up to set email alerts
|

N,N‐ and N,O‐6‐membered Ring peri‐Annelation in Naphthalene. Is it a Heteroring or merely a peri‐ Heterobridge?

Abstract: The effect of peri‐fusion on the aromaticity of 6‐membered N−, O−, N,N−, N,N,N− and N,O‐doped naphthalene derivatives has been studied via NICS‐z, ‐xz, ‐xy, and ‐xyz scans employing DFT and MP2 calculations. The relative aromaticity of these structures was found to vary with the type of heteroring and the distance from the plane. Their corresponding ordering depends on the scan approaches. Accordingly, i) along the z axis at the center of the naphthalene B and C constituent rings, it is 1,8>2>7,9≫4>6, 5>3 (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Dorofeenko et al demonstrated using 1 H NMR in CF3CO2H that 6-methoxy-1H-benzo[de]cinnoline 13 and its N-methyl derivative protonate on C7. 21 © ARKAT USA, Inc (10) with methyl and propyl iodides as well as with benzyl chloride in alkaline medium leads to the formation of the corresponding both N-substituted (11, 39, 40) and 9-substituted cinnoline derivatives (41,42) and also to the dimerization product (43) of the initial compound that corresponds to the formation of a N1-C9 bond (Scheme 3). 22 IR and 1 H NMR spectra were used to establish the structures; remember that protonation takes place at C7 while the alkylation occurs at C9.…”
Section: Acidity and Basicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dorofeenko et al demonstrated using 1 H NMR in CF3CO2H that 6-methoxy-1H-benzo[de]cinnoline 13 and its N-methyl derivative protonate on C7. 21 © ARKAT USA, Inc (10) with methyl and propyl iodides as well as with benzyl chloride in alkaline medium leads to the formation of the corresponding both N-substituted (11, 39, 40) and 9-substituted cinnoline derivatives (41,42) and also to the dimerization product (43) of the initial compound that corresponds to the formation of a N1-C9 bond (Scheme 3). 22 IR and 1 H NMR spectra were used to establish the structures; remember that protonation takes place at C7 while the alkylation occurs at C9.…”
Section: Acidity and Basicitymentioning
confidence: 99%
“…39 Finally, there are two papers by Tsoungas et al in 2018 and 2021. 40,41 on the aromaticity of 1Hbenzo[de]cinnolines and related heterocycles based on NICS calculations, compound 1 being the most aromatic. 43 In the cited work of Tsoungas et al, 44 they analyzed the MEP to indicate that the reactivity of electrophiles towards 1 will occur at positions 3, 6 and 9, which is not the case.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…S23 of the ESI, † where a NICS-xyz scan has been carried out. Note that the NICS-scan identifies local and global ring currents in (poly)cyclic aromatic hydrocarbons and predicts their properties both qualitatively and quantitatively, see 32,33 and references therein. All A X +A X 0 cages, present unusually high magnetic anisotropy, see Fig.…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…In addition, amino‐ and thiophosphates have recently been proposed as plausible molecules in early Earth scenarios [13] . Especially in the context of ligand design, oxidation of P(III) compounds with selenium has many advantages, as the 77 Se NMR spectroscopic parameters such as the 1 J P−Se coupling constant provide important information about the electronic nature of the new phosphines [7c,f,g] …”
Section: Introductionmentioning
confidence: 99%